Interdye Hole Transport Accelerates Recombination in Dye Sensitized Mesoporous Films - Moia,D; Szumska,A; Vaissier,V; Planells,M; Robertson,N; O'Regan,BC; Nelson,J; Barnes,PR (Journal of the American Chemical Society, 2016)
Charge recombination between oxidized dyes attached to mesoporous TiO2 and electrons in the TiO2 was studied in inert electrolytes using transient absorption spectroscopy. Simultaneously, hole transport within the dye monolayers was monitored by transient absorption anisotropy. The rate of recombination decreased when hole transport was inhibited selectively, either by decreasing the dye surface coverage or by changing the electrolyte environment. From Monte Carlo simulations of electron and hole diffusion in a particle, modeled as a cubic structure, we identify the conditions under which hole lifetime depends on the hole diffusion coefficient for the case of normal (disorder free) diffusion. From simulations of transient absorption and transient absorption anisotropy, we find that the rate and the dispersive character of hole transport in the dye monolayer observed spectroscopically can be explained by incomplete coverage and disorder in the monolayer. We show that dispersive transport in the dye monolayer combined with inhomogeneity in the TiO2 surface reactivity can contribute to the observed stretched electron-hole recombination dynamics and electron density dependence of hole lifetimes. Our experimental and computational analysis of lateral processes at interfaces can be applied to investigate and optimize charge transport and recombination in solar energy conversion devices using electrodes functionalized with molecular light absorbers and catalysts.